Multicultural Based Learning Management in Early Childhood Education - Abdullah, Abdullah; Nu'man, Agus; Zamroni, Zamroni; Wahyuni, Dwi Irma; Arbaiyah, Arbaiyah (JURNAL AL-TANZIM, 2022)
This study aims to understand the management of multicultural-based learning at the level of early childhood education. The method used in this study used a qualitative descriptive approach. PAUD Hidayatul Muttaqin conducted this research. In order to get an overview of the object, the researcher made observations at the location and interviewed several components in the school, including; the principal, three teachers, and two guardians. The results showed that multicultural-based learning management was carried out by; planning for multicultural education, strengthening human resources for educators, implementing multicultural education, and evaluating multicultural cultures. The implications obtained through multicultural-based learning management can foster a sense of nationalism and care for others in students. For this reason, the management of multicultural education is a place to instill the spirit of nationalism so that it can unite the existing diversity.